Copper tailing base repairing material as well as preparation method and application thereof

By developing a foundation repair material for copper tailings sand base, it is prepared by mixing specific proportions of copper tailings sand, slag, adhesive and additives, the problems of high cost of foundation repair materials and low efficiency of solid waste absorption are solved, and the material performance is improved and the efficient absorption of solid waste is achieved.

CN119797831APending Publication Date: 2025-04-11TONGLING NONFERROUS METALS GRP TONGGUAN CONSTR & INSTALLATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714682.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In use, existing foundation restoration materials have problems such as high material cost and low solid waste absorption efficiency, especially in the effective utilization of waste such as copper tailings sand.

Method used

A foundation repair material of copper tailings sand base was developed, and the foundation repair material with excellent properties was prepared by mixing copper tailings sand, slag, adhesive and additives in a specific proportion.

Benefits of technology

It reduces the material cost of foundation restoration materials, achieves efficient absorption of solid waste, and improves the compressive strength and dimensional stability of the materials, and is suitable for the field of foundation restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a copper tailing base repairing material, a preparation method and application, and relates to the technical field of base repairing. The copper tailings-based foundation repair material is prepared from the following components: 40-60 wt% of copper tailings; 20 to 40 wt% of muck; 9 to 15 wt% of an adhesive; and 1-5 wt% of an additive. The preparation method comprises the following steps: crushing the copper tailings and the muck, and screening to obtain raw materials with proper sizes; mixing water with an adhesive to form slurry; and the slurry is mixed with copper tailings, muck and an additive, and the copper tailings-based foundation repair material is obtained. The copper tailings-based foundation repair material is applied to the field of foundation repair. The copper tailings are applied to the foundation repair material, the material cost of the foundation repair material is reduced, meanwhile, the purpose of absorbing solid waste is achieved, and by adjusting the formula and the preparation technology of the foundation repair material, the prepared foundation repair material is excellent in performance and low in size shrinkage rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of foundation repair technology, and in particular to copper tailings base foundation repair materials, preparation methods and applications. Background Art

[0002] With the acceleration of industrialization and urbanization, the discharge of solid waste has increased year by year, such as copper tailings, rice husk ash, desulfurization ash, steel slag, etc. The effective utilization of these wastes has become an important issue of environmental protection and resource recycling. As a green building material, foundation repair materials can synergistically dispose of a variety of wastes, realize large-scale consumption of industrial solid waste, slag and mud generated during construction, and reuse them, thereby reducing resource waste and environmental pollution.

[0003] The sandy soil used for backfilling pipelines under the road surface is easy to lose, resulting in underground cavities, which in turn cause urban road collapse. The "mobilization treatment method" effectively solves the problems of difficult backfilling of narrow or irregular spaces and poor construction quality.

[0004] With the deepening of research and engineering practice, foundation repair materials have been used on a large scale in a number of key projects, demonstrating their significant economic, environmental and social benefits in improving backfill quality and disposing of waste earth and rock at construction sites.

[0005] To sum up, the development background of foundation repair materials is not only a positive response to environmental problems, but also an inevitable result of the progress of engineering technology. By effectively utilizing solid waste and solving specific engineering and technical problems, foundation repair material technology has demonstrated its unique value and broad application prospects. Summary of the invention

[0006] In order to solve at least one of the above technical problems, a method for applying copper tailings in foundation repair is developed. The present application provides copper tailings-based foundation repair materials, preparation methods and applications.

[0007] On the one hand, the present application provides a copper tailings base foundation repair material, which is prepared from the following components:

[0008] Copper tailings 40~60wt%;

[0009] Slag 20-40wt%;

[0010] Adhesive 9-15wt%;

[0011] Additives 1~5wt%.

[0012] Optionally, the copper tailings base foundation repair material provided in the present application is prepared from the following components:

[0013] Copper tailings 44-52wt%;

[0014] Slag 30-40wt%;

[0015] Adhesive 9-14wt%;

[0016] Additives 3.5~5wt%.

[0017] Optionally, the size of the copper tailings does not exceed 100 mm; and the moisture content does not exceed 25%.

[0018] Optionally, the size of the slag does not exceed 100 mm; and the moisture content is not less than 13%.

[0019] Optionally, the adhesive uses early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0020] Optionally, the additive is limestone powder.

[0021] In a second aspect, the present application provides a method for preparing the above-mentioned copper tailings base foundation repair material, comprising the following steps:

[0022] S1. Crushing copper tailings and slag, and screening to obtain raw materials of suitable size;

[0023] S2, mixing water and adhesive to form slurry;

[0024] S3, mixing the slurry with the copper tailings, slag and additives crushed in S1 to obtain a copper tailings-based foundation repair material.

[0025] Optionally, in S3, mixing is performed by constant stirring and / or intermittent stirring.

[0026] Optionally, the stirring time for each plate is not less than 2 minutes.

[0027] On the third aspect, the present application provides the application of the above-mentioned copper tailings base foundation repair material in the field of foundation repair.

[0028] In summary, this application achieves the purpose of disposing of solid waste by applying copper tailings to foundation repair materials, while reducing the material cost of foundation repair materials. By adjusting the formula and preparation process of foundation repair materials, the prepared low-grade repair materials have better performance and lower dimensional shrinkage. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.

[0031] Copper tailings: from Tongguan Lujiang Mining Company;

[0032] Muck: from Tongguan Lujiang Mining Company;

[0033] Limestone powder: The main component is calcium carbonate, which comes from Tongling Nonferrous Metals Group;

[0034] Early-strength silicate cement: from Anhui Tongling Conch Cement Co., Ltd.

[0035] Example 1

[0036] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0037] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0038] Mix an appropriate amount of water with 15 kg of cement to form a slurry. Mix the slurry with 40 kg of copper tailings, 40 kg of slag and 5 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0039] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0040] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0041] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0042] The additive used in this embodiment is limestone powder.

[0043] Example 2

[0044] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0045] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0046] Mix an appropriate amount of water with 13.5 kg of cement to form a slurry. Mix the slurry with 42 kg of copper tailings, 40 kg of slag and 4.5 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0047] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0048] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0049] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0050] The additive used in this embodiment is limestone powder.

[0051] Example 3

[0052] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0053] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0054] Mix an appropriate amount of water with 12 kg of cement to form a slurry. Mix the slurry with 44 kg of copper tailings, 40 kg of slag and 4 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0055] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0056] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0057] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0058] The additive used in this embodiment is limestone powder.

[0059] Example 4

[0060] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0061] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0062] Mix an appropriate amount of water with 10.5 kg of cement to form a slurry. Mix the slurry with 46 kg of copper tailings, 40 kg of slag and 3.5 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0063] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0064] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0065] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0066] The additive used in this embodiment is limestone powder.

[0067] Example 5

[0068] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0069] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0070] Mix an appropriate amount of water with 9 kg of cement to form a slurry. Mix the slurry with 48 kg of copper tailings, 40 kg of slag and 3 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0071] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0072] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0073] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0074] The additive used in this embodiment is limestone powder.

[0075] Example 6

[0076] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0077] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0078] Mix an appropriate amount of water with 15 kg of cement to form a slurry. Mix the slurry with 50 kg of copper tailings, 30 kg of slag and 5 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0079] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0080] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0081] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0082] The additive used in this embodiment is limestone powder.

[0083] Example 7

[0084] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0085] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0086] Mix an appropriate amount of water with 14 kg of cement to form a slurry. Mix the slurry with 52 kg of copper tailings, 30 kg of slag and 4 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0087] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0088] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0089] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0090] The additive used in this embodiment is limestone powder.

[0091] Example 8

[0092] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0093] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0094] Mix an appropriate amount of water with 14 kg of cement to form a slurry. Mix the slurry with 54 kg of copper tailings, 30 kg of slag and 2 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0095] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0096] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0097] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0098] The additive used in this embodiment is limestone powder.

[0099] Example 9

[0100] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0101] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0102] Mix an appropriate amount of water with 13kg of cement to form a slurry. Mix the slurry with 56kg of copper tailings, 30kg of slag and 1kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0103] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0104] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0105] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0106] The additive used in this embodiment is limestone powder.

[0107] Example 10

[0108] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0109] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0110] Mix an appropriate amount of water with 14 kg of cement to form a slurry. Mix the slurry with 58 kg of copper tailings, 25 kg of slag and 3 kg of additives in a constant mixing manner, with each mixing time not less than 2 minutes, to obtain a copper tailings-based foundation repair material.

[0111] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0112] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0113] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0114] The additive used in this embodiment is limestone powder.

[0115] Embodiment 11

[0116] This embodiment is used to prepare a copper tailings base foundation repair material, and the details are as follows.

[0117] First, the copper tailings and slag are crushed and screened to obtain raw materials of suitable size.

[0118] Mix an appropriate amount of water with 15kg of cement to form a slurry. Mix the slurry with 60kg of copper tailings, 20kg of slag and 5kg of additives in a constant mixing manner, with each mixing time not less than 2min, to obtain a copper tailings-based foundation repair material.

[0119] The size of the copper tailings used in this embodiment does not exceed 100 mm; the moisture content does not exceed 25%.

[0120] The size of the slag used in this embodiment does not exceed 100 mm; the moisture content is not less than 13%.

[0121] The adhesive used in this embodiment is early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

[0122] The additive used in this embodiment is limestone powder.

[0123] The foundation repair materials prepared in Examples 1 to 11 were poured into a mold with a length, width and height of 1000 mm*100 mm*100 mm to prepare a long strip casting body, and the casting body was subjected to a performance test (test time was 28 days). The results are shown in Table 1.

[0124] Table 1

[0125]

[0126]

[0127] It can be seen from Examples 1 to 11 and Table 1 that the present application uses copper tailings to prepare foundation repair materials, and the compressive strength of the prepared materials at 28 days can reach more than 35 MPa, and the dimensional deviation at 28 days is less than 1%.

[0128] By further analyzing the data in Table 1, it can be seen that when in the technical solution of the present application, the copper tailings are 44-52wt%; the slag is 30-40wt%; the adhesive is 9-14wt%; and the additive is 3.5-5wt%, the compressive strength of the prepared foundation repair material at 28d can reach more than 40MPa, and the dimensional deviation at 28d is less than 0.5%.

[0129] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A copper tailings base foundation repair material, characterized in that: Prepared from the following components: Copper tailings 40~60wt%; Slag 20-40wt%; Adhesive 9-15wt%; Additives 1~5wt%.

2. The copper tailings base foundation repair material according to claim 1, characterized in that: Prepared from the following components: Copper tailings 44-52wt%; Slag 30-40wt%; Adhesive 9-14wt%; Additives 3.5~5wt%.

3. The copper tailings base foundation repair material according to claim 1, characterized in that: The size of the copper tailings does not exceed 100 mm; and the moisture content does not exceed 25%.

4. The copper tailings base foundation repair material according to claim 1, characterized in that: The size of the slag does not exceed 100mm; the moisture content is not less than 13%.

5. The copper tailings base foundation repair material according to claim 1, characterized in that: The adhesive uses early-strength silicate cement with a strength grade of 42.5R, an alkali content controlled at ≤1%, and a moisture content not exceeding 1%.

6. The copper tailings base foundation repair material according to claim 1, characterized in that: The additive is limestone powder.

7. A method for preparing the copper tailings-based foundation repair material according to claim 1, characterized in that: The following steps are involved: S1. Crushing copper tailings and slag, and screening to obtain raw materials of suitable size; S2, mixing water and adhesive to form slurry; S3, mixing the slurry with the copper tailings, slag and additives crushed in S1 to obtain a copper tailings-based foundation repair material.

8. The preparation method according to claim 7, characterized in that: In S3, the mixing is carried out by constant stirring and / or intermittent stirring.

9. The preparation method according to claim 8, characterized in that: The stirring time for each plate should not be less than 2 minutes.

10. Use of the copper tailings base foundation repair material according to claim 1 in the field of foundation repair.